1997
DOI: 10.1007/s000240050092
|View full text |Cite
|
Sign up to set email alerts
|

Delineation of Active Faults, Nucleation Process and Pore Pressure Measurements at Koyna (India)

Abstract: Earthquakes continue to occur in the vicinity of Shivaji Sagar Lake since its creation by the Koyna Dam in 1962. The seismicity peaked in 1967 with a M 6.3 earthquake which claimed over 200 human lives and destroyed the Koyna township. Earthquakes of M`4 occur every year following an increase of water level in the reservoir. During 1973During , 1980During and 1993 earthquakes exceeding magnitude 5 occurred. Most earthquakes of M`4 are associated with pronounced foreshocks and aftershocks. Starting Sepember … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 16 publications
(8 reference statements)
1
15
0
Order By: Relevance
“…7.39b). A similar observation of two seismicity trends was also made by Chadha et al (1997), who relocated the lower magnitude (M<3.0) earthquakes in the region (Fig. 7.40a).…”
Section: Reservoir Induced Seismicity (Koyna Region)supporting
confidence: 81%
See 1 more Smart Citation
“…7.39b). A similar observation of two seismicity trends was also made by Chadha et al (1997), who relocated the lower magnitude (M<3.0) earthquakes in the region (Fig. 7.40a).…”
Section: Reservoir Induced Seismicity (Koyna Region)supporting
confidence: 81%
“…7.40a). , -December, 1994, relocated by Chadha et al (1997); seismic stations are shown by small rectangles, (b) microseismicity, April 1996-December 1997, located by a 10-station digital network (Rai et al, 1999b), and (c) the seismicity with fault plane solutions ).…”
Section: Reservoir Induced Seismicity (Koyna Region)mentioning
confidence: 99%
“…Several researchers have divided the seismic events into discrete clusters based on location, alignments, and focal mechanisms. The westernmost ~NNE tending cluster of events between Koyna and Warna reservoirs has been referred to as the Koyna River Fault Zone (KRFZ) [ Talwani , ; Pandey and Chadha , ; Bhattacharya , ; Dura‐Gomez and Talwani , ; Shashidhar et al , ; Figure 2a], Cluster 1 [ Chadha et al , ; Figure 2a], the Koyna Seismic Zone (KSZ) [ Gahalaut et al , ; Figure 2b], the Northern Escarpment Zone (NEZ) [ Rai et al , ; Srinagesh and Sarma , ; Sarma and Srinagesh , ; Figure 2b], or the North and South Koyna Clusters [ Mandal et al , ; Figure 2c]. Chadha et al [] identified a second (eastern) ~NNE trending cluster of events between Koyna and Warna reservoirs, which they refer to as Cluster 2 (Figure a).…”
Section: Seismicity and Ris Studiesmentioning
confidence: 99%
“…The westernmost ~NNE tending cluster of events between Koyna and Warna reservoirs has been referred to as the Koyna River Fault Zone (KRFZ) [ Talwani , ; Pandey and Chadha , ; Bhattacharya , ; Dura‐Gomez and Talwani , ; Shashidhar et al , ; Figure 2a], Cluster 1 [ Chadha et al , ; Figure 2a], the Koyna Seismic Zone (KSZ) [ Gahalaut et al , ; Figure 2b], the Northern Escarpment Zone (NEZ) [ Rai et al , ; Srinagesh and Sarma , ; Sarma and Srinagesh , ; Figure 2b], or the North and South Koyna Clusters [ Mandal et al , ; Figure 2c]. Chadha et al [] identified a second (eastern) ~NNE trending cluster of events between Koyna and Warna reservoirs, which they refer to as Cluster 2 (Figure a). The earthquake clusters have also been divided into two SE trending clusters of events, the southernmost of which is referred to as the Southern Escarpment Zone (SEZ) [ Rai et al , ; Srinagesh and Sarma , ; Sarma and Srinagesh , ; Figure 2b] and the more northeasterly cluster near Warna Reservoir is referred to as the Warna Seismic Zone (WSZ) [ Rai et al , ; Srinagesh and Sarma , ; Sarma and Srinagesh , ] (Figure b).…”
Section: Seismicity and Ris Studiesmentioning
confidence: 99%
See 1 more Smart Citation